Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.3762/bjnano.9.273
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Au@alendronate nanoparticles as dual chemo-photothermal agent for combined cancer treatment

Abstract: A gold therapeutic nanoplatform with the same molecule used as reductant, coating and therapeutic agent has been developed in a one-pot, one-phase process using alendronate, a drug from the bisphosphonate family known for its antitumor effects. In addition, the core made of gold nanoparticles (NPs) brings thermal functionalities under irradiation within the first biological window (650–900 nm). The Au@alendronate nanoplatform thus provided a combined antitumor activity through drug delivery and photothermal th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Silver-gold hollow nano shells with mesoporous silica nanoparticle have been utilized for the PDT in the experimental PC cells [158]. In another study, a hybrid nanoparticles of Au-alendronate were made for combined PDT-chemotherapy of PC [159]. The PDT not only enhanced the impact of chemotherapy in suppressing PC, but also decreased the dose of the chemotherapy needed for the treatment of PC [160][161][162].…”
Section: Phototherapymentioning
confidence: 99%
“…Silver-gold hollow nano shells with mesoporous silica nanoparticle have been utilized for the PDT in the experimental PC cells [158]. In another study, a hybrid nanoparticles of Au-alendronate were made for combined PDT-chemotherapy of PC [159]. The PDT not only enhanced the impact of chemotherapy in suppressing PC, but also decreased the dose of the chemotherapy needed for the treatment of PC [160][161][162].…”
Section: Phototherapymentioning
confidence: 99%
“…Furthermore, the tunable size and shape of GNPs is related to a higher photothermal conversion efficiency [162,164]. Finally, the easy surface functionalization of GNPs allows their use as dual photothermal and chemotherapeutical agents [165], which in consequence, leads to a more efficient reduction of the tumor mass. In this regard, it has been reported that GNP-mediated PTT sensitizes tumor cells to other drugs [162], thus reducing their necessary dose or even overcoming drug resistance.…”
Section: Gold As a Vehicle: Biomedical Potential Of Gold Nanopartimentioning
confidence: 99%
“…In vitro hyperthermia tests showed efficiency in inoculating mouse breast cancer cells. Another study reports the use of alendronate-coated gold nanoparticles [34]. The resulting gold-alendronate nanoplatform combines antitumor activity through drug delivery and photothermal therapy, as illustrated in vitro on the inhibition of prostate cancer cells.…”
Section: Healthmentioning
confidence: 99%